2007
DOI: 10.1051/0004-6361:20066667
|View full text |Cite
|
Sign up to set email alerts
|

Obscured and unobscured AGN populations in a hard-X-ray selected sample of the XMDS survey

Abstract: Aims. Our goal is to probe the populations of obscured and unobscured AGN investigating their optical-IR and X-ray properties as a function of X-ray flux, luminosity and redshift within a hard X-ray selected sample with wide multiwavelength coverage. Methods. We selected a sample of 136 X-ray sources detected at a significance of ≥3σ in the 2−10 keV band (F 2−10 > ∼ 10 −14 erg cm −2 s −1 ) in a ∼1 deg 2 area in the XMM Medium Deep Survey (XMDS). The XMDS area is covered with optical photometry from the VVDS an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
48
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 104 publications
(173 reference statements)
10
48
1
Order By: Relevance
“…Lowering the threshold for X-ray absorbed AGNs to log N H =21.5 cm −2 increases the frequency to 20%, so we can confidently say the X-ray absorbed fraction within Type 1 AGNs is between 10% and 20%. These fractions are more in agreement with the results of Perola et al (2004) and nearly a factor of 3 smaller than the rates found by Tajer et al (2007) and Merloni et al (2014). What is further clear from this study is that the hydrogen column densities measured from the X-ray spectra are generally much larger than those measured from the BLR extinction, assuming a Galactic GDR.…”
Section: ( )supporting
confidence: 85%
See 2 more Smart Citations
“…Lowering the threshold for X-ray absorbed AGNs to log N H =21.5 cm −2 increases the frequency to 20%, so we can confidently say the X-ray absorbed fraction within Type 1 AGNs is between 10% and 20%. These fractions are more in agreement with the results of Perola et al (2004) and nearly a factor of 3 smaller than the rates found by Tajer et al (2007) and Merloni et al (2014). What is further clear from this study is that the hydrogen column densities measured from the X-ray spectra are generally much larger than those measured from the BLR extinction, assuming a Galactic GDR.…”
Section: ( )supporting
confidence: 85%
“…Under the simple picture of a static dusty torus around an AGN, both optical and X-ray measurements of the gas column density should agree. To a large extent this is true, as many studies find that Type 1 AGNs show little to no X-ray absorption, while most Type 2 AGNs are X-ray absorbed with N H 10 22 cm −2 (e.g., Smith & Done 1996;Turner et al 1997;Risaliti et al 1999;Garcet et al 2007;Mainieri et al 2007;Tajer et al 2007;Antonucci 2012;Malizia et al 2012;Merloni et al 2014;Davies et al 2015) in accordance with the unified model. Of course, the unified model, while broadly successful in explaining the diversity of AGNs, is simplified and investigations of differences between Type 1 and Type 2 AGNs that cannot be explained by this paradigm can help to reveal the complex nature of AGNs.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Figure 4 shows the distribution of HR for the sources selected as Type-1 and Type-2 as described above. As expected, these results indicate that the selected Type-2 AGN have a higher hardness ratios than the Type-1 AGN population, due to their higher column densities (Tajer et al 2007). Sazonov & Revnivtsev (2004) have estimated column densities from the flux ratio F [8−20] /F [3−8] , where F [8−20] and F [3−8] are the flux measurements in the [8][9][10][11][12][13][14][15][16][17][18][19][20] and [3][4][5][6][7][8] keV X-ray bands respectively.…”
Section: Extinction Correctionsupporting
confidence: 82%
“…2.1). Following Tajer et al (2007), we define the hardness ratio as HR = (CR H − CR S )/(CR H + CR S ), where CR H and CR S are the count rates in the hard [2-10] and soft [0.5-2] keV band, respectively. Figure 4 shows the distribution of HR for the sources selected as Type-1 and Type-2 as described above.…”
Section: Extinction Correctionmentioning
confidence: 99%